Effectiveness of Diabetes Daily Care Calculator Application on Self-Management of Type 2 Diabetes Mellitus Patients - Surya, Defrima Oka; Desnita, Ria; Thohir, Ilham (Indonesian Journal of Global Health Research, 2024)
Type 2 DM can affect aspects of the sufferer's quality of life and carries a risk of complications. DM requires good self-management to be able to control glucose levels. Education is an important component in patient self-management so that patients can control their disease. Smartphone technology through application implementation can be utilized to create innovative solutions. This research develops and applies a daily care diabetes calculator based on a mobile application that provides information on the pillars of diabetes management that is easily accessible to patients and embeds a smart calculator to calculate diet based on the patient's calorie needs and physical activity. The aim of the research is to determine the effectiveness of applying the daily care diabetes calculator application for self-management of Type 2 Diabetes Mellitus patients. This type of quantitative research with a quasi-experiment design uses a one group pre and posttest approach without control group. The research was conducted at RSUD dr. Rasidin. Sampling was taken using a consecutive sampling technique with a sample size of 22 people. The intervention was given for 2 weeks and self-management was assessed using the The Summary of Diabetes Self-care Activities (SDSCA) questionnaire. with the validity and reliability test values for thisinstrument being r = 0,80 and α : 0,74. Data analysis using paired t test The average self-management score before implementing the diabetes daily care calculator application was 40.32 and the average self-management score after was 63.18. Implementation of a daily care diabetes calculator based on a mobile application is effective in improving self-management of type 2 diabetes mellitus patients (p<0.05). This application can be used by nurses as an extension in caring for patients at home, so that the care process provided remains sustainable.